(untitled) (World Bulletin of Public Health, 2023)
The relevance of early diagnosis and determination of the risk of developing pronounced vestibular disorders is an equally important task, since in children and adolescents with type 1 diabetes mellitus it can have a great impact on the quality of life, further choice of profession and will help to avoid disability in children as the underlying disease progresses.